Psychological health status among former residents of Tomioka, Fukushima Prefecture and their intention to return 8 years after the disaster at Fukushima Daiichi Nuclear Power Plant - Orita, Makiko; Mori, Keisuke; Taira, Yasuyuki; Yamada, Yumiko; Maeda, Masaharu; Takamura, Noboru (Journal of Neural Transmission, 2020)
The present study aimed to clarify the psychological status of 766 former residents of Tomioka Town, Fukushima Prefecture, and their intent to return (ITR) 8 years after the disaster at Fukushima Daiichi Nuclear Power Plant. We investigated their ITR home and their perception of the risk of health effects from radiation exposure. We also evaluated rates of post-traumatic stress disorder (PTSD) using a PTSD checklist (PCL-S) and of psychological stress using the patient health questionnaire-9 (PHQ-9). Among the residents, 102 (13%) had returned home (group 1), 214 (28%) were unsure about returning (group 2), and 450 (59%) had decided not to return (group 3). Concern about exposing the next generation to radiation was significantly more prevalent in groups 2 and 3 than in group 1. The frequency of positive PCL-S and PHQ-9 responses was higher in group 2 than in groups 1 and 3. Factors that were independently associated with returning to Tomioka were positive PCL-S (OR, 4.3) and PHQ-9 (OR, 2.2) scores, concerns about consuming locally sourced food, and living with children, and were more prevalent in group 2 than group 1 (reference). Group 2 was more anxious about radiation exposure and health effects, and had higher rates of psychological stress and PTSD. Providing support to such residents through careful risk communication will be required to recover this community after the nuclear disaster.